علاقة التدين بالرضا الزواجي من خلال الذكاء العاطفي والمسؤولية الاجتماعية في محافظة الداخلية في سلطنة عمان - سيابي، عبد الرحمن محمد سالم (Kulliyah of Education, International Islamic University Malaysia, 2021)
The study aimed to identify the relationship of religiosity with marital consent through emotional intelligence and social responsibility in the Governorate of the Interior in the Sultanate of Oman, and the study relied on the relational descriptive approach. The social responsibility scale, the religiosity scale, and the marital satisfaction measure, and the study population consisted of (489) married couples, using statistical methods (SPSS) program, and modeling the structural equation (SEM) using the AMOS program, where The results of the study showed the presence of a positive relationship between religiosity and emotional intelligence, the presence of a positive relationship between religiosity and social responsibility, the existence of a positive relationship between social responsibility and marital satisfaction, the presence of a positive relationship between the relationship of emotional intelligence and social responsibility, and the presence of a positive relationship between emotional intelligence and marital satisfaction, and the presence of a positive relationship Between religiosity and marital satisfaction.